Surgical and Medical Applications of Drones: A Comprehensive Review - Rosser, James C.; Vignesh, Vudatha; Terwilliger, Brent A.; Parker, Brett C. (Journal of the Society of Laparoendoscopic Surgeons, 2018)
Drones have the ability to gather real time data cost effectively, to deliver payloads and have initiated the rapid evolution of many industrial, commercial, and recreational applications. Unfortunately, there has been a slower expansion in the field of medicine. This article provides a comprehensive review of current and future drone applications in medicine, in hopes of empowering and inspiring more aggressive investigation. A literature search was performed by EBSCO (Elton B. Stephens Company) Discovery Service, searching the phrases "drones," "UAV," "unmanned aerial vehicles," "UAS," and "unmanned aerial systems." A second search was used to identify sources that contained "drone" in the subject or title and "medicine" in any of the text, yielding 60,260 results. After screening for irrelevant material, 1296 sources remained applicable. Major themes and number of sources were as follows: 116 public health and medical surveillance, 8 telemedicine, and 78 medical transport systems. Drones are used for surveillance of disaster sites and areas with biological hazards, as well as in epidemiology for research and tracking disease spread. Telecommunication drones are being used for diagnosis and treatment, perioperative evaluation, and telementoring in remote areas. Drones have the potential to be reliable medical delivery platforms for microbiological and laboratory samples, pharmaceuticals, vaccines, emergency medical equipment, and patient transport. Government agencies have placed drone use on the national agenda. The next steps include aggressive research initiatives in the areas of safety, industry expansion, increased public awareness, and participation.